Landscape to microhabitat: Uncovering the multiscale complexity of native and exotic forests on Terceira Island (Azores, Portugal) - Sébastien Lhoumeau; Rui B. Elias; Dominik Seidel; Rosalina Gabriel; Paulo A. V. Borges (PLoS ONE, 2025)
This study aims to identify the structural and compositional differences between native and exotic woodlands on Terceira Island, Azores. Based on landscape, habitat, and microhabitat analyses, remnants of native forests appeared to be associated with less accessible terrains. A more homogeneous structural complexity is exhibited, derived from the numerous branching patterns of the endemic vascular plant species. In contrast, exotic forests exhibit structural heterogeneity driven by mixed non-indigenous vascular plant species as a result of human actions such as afforestation and latter invasion of exotic tree species, after abandonment of the agricultural use. The ground and canopy layers in exotic forests were more invaded by non-indigenous species, while the understory demonstrated greater resilience by being mostly composed of indigenous species. Our findings highlight the structural and ecological differences between native and exotic woodlands, reflecting the historical transformation of forest cover in the Azores. These insights emphasize the importance of long-term monitoring and structural assessments in informing conservation efforts aimed at preserving native forests and managing invasive species in exotic woodlands.